Effectiveness of Jazz Instrumental Music Therapy in Reducing Pain Intensity in Abdominal Pain Patients in the Emergency Room of Gatot Soebroto Army Hospital - Defiany Nabilah; Bahreni Yusuf (JOURNAL EDUCATIONAL OF NURSING(JEN), 2026)
Abdominal pain is one of the primary complaints of patients visiting the Emergency Room, requiring rapid and appropriate pain management. In addition to pharmacological therapy, non-pharmacological interventions such as instrumental jazz music therapy can be used as a distraction and supportive therapy because it is safe, easy to implement, and has no side effects. To determine the effectiveness of instrumental jazz music therapy in reducing pain intensity among patients with abdominal pain in the Emergency Room of RSPAD Gatot Soebroto. This study used a case study design involving four cases selected from the Emergency Room with complaints of abdominal pain. The sample consisted of patients experiencing acute abdominal pain in the Emergency Room, selected based on predetermined inclusion and exclusion criteria. The intervention provided was instrumental jazz music therapy administered once daily for 10 minutes using audio media with earphones. Pain intensity was measured before and after the intervention using the Wong-Baker Pain Rating Scale, accompanied by observations of patients’ physiological and behavioral responses during therapy. The results demonstrated a reduction in pain intensity following the administration of instrumental jazz music therapy. This case study concludes that instrumental jazz music therapy can be effectively used as a non-pharmacological nursing intervention to reduce pain intensity in patients with abdominal pain in the Emergency Room.